Prevalence of Insomnia in patients suffering from Stroke - Iftikhar Ahmad, Hafiz; Rafique, Hira; Mushtaq, Maida; Uzair Asghar, Hafiz Muhammad; Maqbool, Sania; Mushtaq, Qurratulain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To establish the Prevalence of insomnia in patients suffering fromstroke. Methods: By the consent of patients or their attendants we piloted a cross-sectional study among90 stroke patients at different hospitals of Lahore. A modified Sleep Centre Interview wasconducted from the participants regarding their sleeping pattern, day time effects and its effecton their life. Results: The study included 90 stroke patients of those 56 were males and 34 were females. Outof 90, 27(30%) patients had sleep disturbance of them 16 were male and 11 were male.Therefore the prevalence of insomnia was found to be 30%. There were 33.3% patients reportedthat they woke up at least 2 time at night while 25.9% woke up 3 times at night and only 18.5%woke up once at night. 48.4% patients reported that they follow the same sleep pattern for 3-4. days per week while 44.4% followed the sleep pattern for 2-3 days a week 74% reported that ittakes them 2-3 hours to sleep while 22.2% reported that it takes them 4-5 hours to sleep once awaked. Conclusion: The study concluded that sleep disturbances as insomnia and hyper insomnia arecommon among stroke fighters. Insomnia was associated with increased level of anxiety anddisability after stroke. Physical therapy and psychotherapy will improve patient’s level of cognition,energy level, and mood and give them better sleep.